Floristic Names in V. Lazaruk’s Collection of Poetry “Litoral”: Functional and Stylistic Aspects (Linguostylistic Studies, 2021)
The article elucidates the issue of phytonomes revealed in the poetic collection “Litoral” by Victor Lazaruk and analyzes the semantic and stylistic potential of these lexemes with an emphasis on the functional and stylistic features of floral names in terms of the poetic speech units.The phytonomes that occur in the poetic collection of Victor Lazaruk’s “Litoral” form a rich in repertoire thematic group of vocabulary. The degree of signifiers' representation in it is various. Fixed in the collection florolexemes are divided into several lexical and semantic subgroups: dendro-lexemes (trees, shrubs/bushes), names of herbaceous plants, and crops. The total number of the recorded units is 83 (33 names of woody plants, 44 names of herbaceous plants, 6 names of crops).The functional activity of the lexical-semantic group of florolexemes can be illustrated by the following quantitative indicators: total – 242 word usage; dendro-lexemes – 142 word usage; names of herbaceous plants – 88 word usage; crops – 12 word usage. Dendro-lexemes birch (29 fixations) and oak (20 fixations) demonstrate the highest frequency level.The case study material testifies to the productivity of flora-lexemes in the function of style-semes and expressemes with a wide emotional and evaluative potential. The figurative meaning of phyto-names is always a matter of the author’s individual comprehension.The study has revealed that most of these floral names are distinguished by positive-emotional and minor coloration. In numerous landscape descriptions, flora-lexemes are organically woven into the linguistic and poetic structure of the text. They create a distinct local-national coloring of the image, characterize the seasonal changes of nature, symbolize the attributes of space, embody the unity of generations, glorifying the glorious past and giving faith in a bright future.
Keywords: lexeme; floronomens; symbol; personification; metaphor